PENDIDIKAN KARAKTER DALAM FILSAFAT PENDIDIKAN ISLAM - Batu Bara, Liza Handayani; Tajibu, Kamaluddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to understand the implementation of character education in the philosophy of Islamic education. This research uses a qualitative method with a library research approach, data collection method is by documentation, namely by collecting books. From the data collected, the results of this research can be concluded that character education from the perspective of Islamic educational philosophy is implemented into curriculum design using several methodologies, namely First, the Exemplary Method. Second, the Stories Method. The Three Methods of Advice. Fourth Method of Habituation. The Five Methods of Punishment and Reward. The Six Methods of Lectures (Khutbah). And the Seven Discussion Methods. This method is also considered by the Al-Quran in educating and teaching people with the aim of further strengthening their understanding and attitude towards a problem